Penerapan Just in Time dalam Sistem Pembelian dan Sistem Produksi - Heri Sukendar W. (Bina Nusantara University, 2011)
Just in Time is a management philosophy, techniques, or methods be comprehensive in order to buy raw materials and producing goods only when necessary and timely to be used at every stage we have available. Research was conducted by doing library research. Many problems faced by the industry, especially the existence of inefficiency in the system of purchasing and production. With the implementation of Just in Time, then the problem can be overcome and eventually going savings that will increase corporate profits.